Chemotherapy for breast cancer during pregnancy induces vascular alterations and impaired development of placental villi: A preliminary histopathological study. (July 2020) - Del Gobbo, Alessandro; Scarfone, Giovanna; Peccatori, Fedro Alessandro; Villa, Antonella; Ossola, Wally; Ercoli, Giulia; Bosari, Silvano; Ferrero, Stefano; Boggio, Francesca Laura; Grossi, Elena; Cribiù, Fulvia Milena
Abstract: Objective: To evaluate histological alterations in placentas of women affected by breast cancer and treated with chemotherapy during pregnancy. Study design: We retrospectively reviewed histological slides of 23 placentas of patients affected by breast cancer and treated with chemotherapy during pregnancy and 23 control placentas of women without breast cancer and with physiological pregnancies of the same gestational age. Results: All the patients had breast ductal infiltrating carcinoma, 19 of 23 cases had a G3 cancer. All patients were treated with 2–6 cycles of chemotherapy starting after 16 weeks of gestation, with different protocols. No hypertensive complications and no pre-eclampsia episodes were observed; birth weight was consistent with gestational age in all babies in both group with no uneventful outcomes and no perinatal mortality or fetal malformations. Twenty out of 23 cases (86 %) showed hypoxia-induced villous alterations, including increased syncytial knotting (Tenney-Parker changes), perivillar fibrin deposits, distal villous hypoplasia or accelerated maturation and focal villous chorangiosis. These alterations were found in 19 out of 23 controls (83 %), with no statistically significant difference between the two groups. Conclusions: These results shows that chemotherapy in the second and third trimester of pregnancy may lead to non-specific alterations in placental vasculature and morphology.